Evaluation of Novel Approaches to Software Engineering 8th International Conference, ENASE 2013, Angers, France, July 4-6, 2013, Revised Selected Papers - Filipe, Joaquim; Maciaszek, Leszek A.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the thoroughly refereed proceedings of the 8th International Conference on Evaluation of Novel Approaches to Software Engineering, ENASE 2013, held in Angers, France, in July 2013. The 18 full papers presented were carefully reviewed and selected from 46 submissions. The papers reflect a growing effort to increase the dissemination of new results among researchers and professionals related to evaluation of novel approaches to software engineering. By comparing novel approaches with established traditional practices and by evaluating them against software quality criteria, the ENASE conferences advance knowledge and research in software engineering, identify most hopeful trends, and propose new directions for consideration by researchers and practitioners involved in large-scale software development and integration.
Designing a virtual reality software -- An experiment on self-configuring database queries -- Automated COSMIC-based analysis and consistency verification -- An MDE approach to develop mobile-agents applications.
Keywords: Computer science; Software engineering; Logic design; Information Systems; Management information systems; Computer Science; Software Engineering; Logics and Meanings of Programs; Business Information Systems; Programming Languages, Compilers, Interpreters; Information Systems Applications (incl. Internet).; Management of Computing and Information Systems